2021
DOI: 10.3390/ijerph18020623
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Electric Vehicle Policies on Environment and Health in the Beijing–Tianjin–Hebei Region

Abstract: China is implementing intensive policies on electric vehicles to control air pollution in urban regions, especially the Beijing–Tianjin–Hebei (BTH) region, one of the most polluted areas in China. The development of electric vehicles will lead to an increase in electricity demand. Because electricity is mostly generated by thermal power in China, primary energy consumption will also increase. This study sets two scenarios: with the electric vehicle policies scenario (REN) and without the electric vehicle polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…The negative impact of electric vehicles (e.g., BEVs and PHEVs) on PM2.5 emissions were found by several authors (e.g., Rangaraju et al [10]; Timmers and Achten [11]; Alam et al [12]; Vilchez et al [13]; Xiong et al [14]; Ajanovic and Haas [15]; Wang et al [16]; Vilchez and Jochem [17]; Wang et al [18]; Andersson and Börjesson [19]; Zhao et al [20]; and Ma et al [21]). According to Ajanovic and Haas [15], electric vehicles (e.g., BEVs and PHEVs) can mitigate environmental degradation.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The negative impact of electric vehicles (e.g., BEVs and PHEVs) on PM2.5 emissions were found by several authors (e.g., Rangaraju et al [10]; Timmers and Achten [11]; Alam et al [12]; Vilchez et al [13]; Xiong et al [14]; Ajanovic and Haas [15]; Wang et al [16]; Vilchez and Jochem [17]; Wang et al [18]; Andersson and Börjesson [19]; Zhao et al [20]; and Ma et al [21]). According to Ajanovic and Haas [15], electric vehicles (e.g., BEVs and PHEVs) can mitigate environmental degradation.…”
Section: Discussionmentioning
confidence: 88%
“…Under two alternative scenarios, a 52% to 69% reduction in CO 2 is possible, while only a 9% to 15% reduction in PM2.5 by 2035 is achievable. Ma et al [21] investigated the impact of electric vehicle policies on the environment in the Beijing-Tianjin-Hebei District under two scenarios. The results showed that under the electric vehicle policy (REN) scenario, PM2.5 emissions will decrease by 18.84%, 20.04% and 19.57% by 2030 in Beijing, Tianjin, and Hebei, respectively.…”
Section: The Effect Of Electric Vehicles On Pm25 Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing blockades, especially of diesel cars, and the development of green strategies in the automotive sector have led to a growing interest in hybrid and electric cars [4,5]. The main reason for this is that these vehicles save on fuel costs and, additionally, because of their potentially large contribution to environmental protection [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of NEVs within Chinese cities has been shown to deliver considerable improvements to local air quality if done at scale. This can yield considerable benefits to local public health and economic activity(Ma, Madaniyazi & Xie, 2021). 12 In the context of this paper, BEVs and PHEVs are the focal point when referring to Chinas NEV policies.…”
mentioning
confidence: 99%